Your guide to pre-schools in Metro Manila - De Ocampo, Maricar Gustilo (Pasig City Anvil Pub., 2001)
It provides reports on over 100 pre-schools in Metro Manila. It has a section on special children which contains discussions of their particular problems and needs, as well as a listing of Metro Manila pre-schools that can help them.
Keywords: Education, Preschool -- Philippines -- Manila Metropolitan Area -- Directories; Early childhood education -- Philippines -- Manila Metropolitan Area -- Directories; Preparatory schools -- Philippines -- Manila Metropolitan Area -- Directories; Special education -- Philippines -- Manila Metropolitan Area -- Directories